2018
DOI: 10.3350/cmh.2018.0034
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diastolic dysfunction predicts poor prognosis in patients with decompensated liver cirrhosis

Abstract: The presence of LVDD is associated with poor survival in patients with decompensated LC. Therefore, it may be important to monitor and closely follow LVDD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 26 publications
(42 reference statements)
4
38
0
1
Order By: Relevance
“…Several studies have shown that patients with an increased left atrial (LA) dimension, a higher E/e′ ratio or the presence of diastolic dysfunction on echocardiography were associated with poor survival. 1 , 2 , 5 , 6 , 22 However, other studies showed that the echocardiographic parameters were not associated with mortality and the only independent predicting factor for mortality was the Child-Pugh score or MELD score. 11 , 23 Possible reasons for these discrepancies between these studies include different enroll criteria, different follow-up time, and differences in the cause of cirrhosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have shown that patients with an increased left atrial (LA) dimension, a higher E/e′ ratio or the presence of diastolic dysfunction on echocardiography were associated with poor survival. 1 , 2 , 5 , 6 , 22 However, other studies showed that the echocardiographic parameters were not associated with mortality and the only independent predicting factor for mortality was the Child-Pugh score or MELD score. 11 , 23 Possible reasons for these discrepancies between these studies include different enroll criteria, different follow-up time, and differences in the cause of cirrhosis.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, some studies have investigated the correlation of echocardiographic parameters and patient outcomes, with diastolic dysfunction being the most evident factor for predicting outcomes. 1 , 2 , 5 , 22 Nevertheless, these studies showed discordant results on echocardiography in predicting outcomes. 11 , 23 In the present study, we found that there was no association between echocardiographic parameters and the occurrence of death at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Prevalence of DD among patients with dyspnea is uncertain 20,21. Both presence of DD and its severity have independent prognostic implication 3,20,22,23. Exercise‐induced elevation in filling pressures may cause symptoms in grade 1 DD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Clinical and Molecular Hepatology , a Korean prospective study by Lee et al implicates that the presence of left ventricular diastolic dysfunction (LVDD), which is an early manifestation of CCMP, is associated with poor survival in patients with decompensated cirrhosis [7]. Seventy patients with decompensated cirrhosis were enrolled prospectively and cardiac function of the study patients was assessed using 2D echocardiography with tissue Doppler imaging.…”
mentioning
confidence: 99%
“…In a study by Lee et al, there was no difference in liver function index (Child-Pugh class and MELD score) according to the presence or absence of LVDD [7]. Recently, an European prospective, multicenter study investigating the presence of diffuse myocardial fibrosis in cirrhotic patients using cardiac magnetic resonance (CMR) was reported [8].…”
mentioning
confidence: 99%